Selective synthesis using ETFBO: a new strategy for the preparation of hexahydro‐1H‐pyrrolo[1,2‐c]imidazol‐1‐one. - Faillace, Martín Sebastián (2023)
In this work, we report the regiospecific and stereoselective synthesis of novel pyrrolo thioxoimidazolidinones with promising biological activities due to the inherent pharmaceutical properties of thioxoimidazolidinone core. The reaction of different thioxoimidazolidinones with trans-4-ethoxy-1,1,1-trifluorobut-3-en-2-one (ETFBO) yields bicyclic 1,3-diaza heterocycles bearing the trifluoromethyl (CF3) moiety. Our investigation involved both depth experimental analysis and theoretical calculations to fathom out the mode of reaction of this building block and elucidate the underlying mechanism operating for the observed reactions. Remarkably, this unusual mechanism retained the ethanol moiety from the building block in the final products, deviating from conventional nucleophilic reactions reported in the literature.